The Effectiveness of the Use of Nurse Safety Booklet on Nurse Knowledge in Ergonomic Injury Prevention in BIMA Hospital (International Journal of Studies in Nursing, 2019)
Safety has become a global issue in various sectors, including the health services sector. The hospital is one of the health service organizations that is guided to continuously improve quality by building safer and safer health services so as to get customer loyalty. Hospital staff is a major component of quality management in one of the indicators in evaluating hospital accreditation. This research uses a quasi-experimental research design pre and posttest with control group. Quasi experiment research is a study that tests an intervention in a group of research subjects and then measures the results of the intervention. Samples in this study are all nurses who are in the room of the General Hospital, Surgery and ICU Bima Hospital, which are 50 people. The results showed the results of different tests using paired t-test p value = 0.000 which can be concluded that there are differences between the intervention group and the control group, seen from the value of the difference in the intervention group is greater than the difference in the control group can be interpreted as education using more booklets affect the increase in nurse knowledge. The conclusion in this study was that there were significant differences in nurses' knowledge after being given education using pre and post intervention booklets between the intervention and control groups (p = 0.000).